Design and optimization of a hetero-junction solar cell using Silvaco software packages - Osman, Muhammad fairuz (2006)
In this paper, the design and optimization of a hetero-junction solar cell, utilizing a simulation using Silvaco software packages have been demonstrated. This paper has investigated the design of a hetero-junction solar cell. In this study, a hetero-junction of GaAs/AlGaAs solar cell and a single p-n junction Si solar cell were simulated. Firstly, fundamentals of solar cell operation and performance have been presented. The basic advantage and operation of hetero-junction solar cells were discussed. Then, the important design issues have also been discussed. The simulation of the solar cells using Silvaco TCAD Tools consisted of processes simulation of constructing solar devices in ATHENA and simulation of electrical characteristics of solar devices in ATLAS. The results from both simulations of the hetero-junction of GaAs/AlGaAs solar cell and a single p-n junction Si solar cell were analyzed to compare their performances. Then, the paper was concluded with an argument that the design of hetero-junction solar cells will be improved in the future and the technology can become a feasible widespread power source. Finally, the future design improvements have been suggested.